“All I want to do is get that check and get drunk”: Testifying to resistance in Charles Bukowski's Factotum - Carl Rhodes (Journal of Organizational Change Management, 2009)
Purpose – The purpose of this paper is to examine the themes of resistance to organizations in Charles Bukowski's novelFactotum in relation to contemporary theory in organization studies, and to consider the ways in which the literary depiction of resistance can be used to extend theoretical debates on the subject. Design/methodology/approach – Literary fiction, and the novel in particular, is theorized as an undecidable space between experiential reality and creative/fictional experiment that offers a valuable exposition of and experimentation with, the meaning of work in organizations. The theme of resistance to organizations inFactotum is read in terms of how the experiment of the novel can be articulated with discussions of resistance in organization studies. Findings – The paper shows how Bukowski's novel portrays a form of resistance that has elided attention in the organization studies literature – that which is highly individualistic and disorganized yet extreme and overt. This is a resistance that does not just work against the power structures of one organization, but rather rejects all aspects of capitalist work relations other than those necessary for survival. Originality/value – Theoretically, the paper extends theories of resistance in organizations by usingFactotum to explore the meaning of extreme individualised organizational resistance. Methodologically the paper exemplifies how the reading of novels can provide insight to the paper of organizations not available through more conventional means by testifying to, and experimenting with, the meaning of organizational experience. <!-- InstanceEndEditable -->